ChemInform Abstract: Gold(I)‐Catalyzed Decarboxylation of Propargyl Carbonates: Reactivity Reversal of the Gold Catalyst from π‐Lewis Acidity to σ‐Lewis Acidity. Issue 33 (August 2015) - Shen, Ruwei; Yang, Jianjun; Zhu, Shugao; Chen, Chao; Wu, Luling
Abstract In the catalyzed decarboxylative etherification of propargyl carbonates the gold(I) catalyst shows a distinct σ‐acidity and propargyl ethers are furnished.